COVID-19 and the burning issue of drug interaction: never forget the ECG. Issue 1145 (20th August 2020) - Sciaccaluga, Carlotta; Cameli, Matteo; Menci, Daniele; Mandoli, Giulia Elena; Sisti, Nicolò; Cameli, Paolo; Franchi, Federico; Mondillo, Sergio; Valente, Serafina
ABSTRACT: The coronavirus disease of 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), has been rapidly escalating, becoming a relevant threat to global health. Being a recent virus outbreak, there are still no available therapeutic regimens that have been approved in large randomised trials and so patients are currently being treated with multiple drugs. This raises concerns regarding drug interaction and their implication in arrhythmic burden. In fact, two of the actually used drugs against SARS-CoV2, such as chloroquine and the combination lopinavir/ritonavir, might determine a QT (the time from the start of the Q wave to the end of the T wave) interval prolongation and they show several interactions with antiarrhythmic drugs and antipsychotic medications, making them prone to an increased risk of developing arrhythmias. This brief review focuses the attention on the most relevant drug interactions involving the currently used COVID-19 medications and their possible association with cardiac rhythm disorders, taking into account also pre-existing condition and precipitating factors that might additionally increase this risk. Furthermore, based on the available evidence and based on the knowledge of drug interaction, we propose a quick and simple algorithm that might help both cardiologists and non-cardiologists in the management of the arrhythmic risk before and during the treatment with the specific drugs used against SARS-CoV2.